Process variety modeling using colored object-oriented petri-nets with changeable structures (COPN-CS) - Kannan Prasanna. (2008)
This dissertation proposes a modeling tool, Colored Object-oriented Petrinet with changeable structures (COPN-CS) to deal with and solve the problems that arise when handling product variety in manufacturing processes during production planning.